Analysis of Principals' Managerial Transformational Leadership: Teachers' Digital Literacy in Elementary Schools - Khairunnisa, Salsabila; Fatayan, Arum; Fetrimen, Fetrimen (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
Educational change requires teachers to be more digitally literate due to rapid technology development. This adjustment is difficult for some teachers, especially elementary school teachers. This research is driven by the principal's transformative leadership and managerial talents in guiding this transition. The purpose of this study is to analyze the principal's managerial strategy, how the principal improves teachers' digital literacy, teachers' perceptions of the principal's transformational leadership style, and the obstacles faced by teachers in improving digital literacy. This study uses a qualitative approach with a case study method. The research subjects consisted of the principal, teachers at various levels, and administrative staff. Data sources were obtained through in-depth interviews, field observations, and documentation. The research instruments were interview guidelines and observation sheets. The data analysis technique used was the interactive model of Miles, who plays, which consists of data reduction, data presentation, and drawing conclusions. Data validity was maintained through triangulation techniques for data sources and methods. The findings of this study demonstrate that the principal has adopted a transformational leadership style by offering motivation, serving as a role model, and fostering collaboration among teachers. However, some teachers have encountered resistance due to age, time constraints, and a lack of confidence in using digital devices. School principals continue to make various efforts to overcome these obstacles so that teachers' digital literacy can improve sustainably.